Read & think French - Think French magazine (New York McGraw-Hill Education, 2017)
This text features 100-plus engaging, easy-to-read articles written by native French-speakers. As the you move through the text, you will gain confidence with the French language and build a vocabulary of key French words and phrases.
Culture -- Voyages -- Tradition -- Célébration -- Biographie -- Coutumes -- Les arts -- Histoire -- Géographie -- Gastronomie
"Audio recordings for select readings and flashcards for all vocabulary lists are available to support your study of this book. Go to www.mhlanguagelab.com to access the online version of the application."--Title page verso.
Keywords: French language -- English. -- Textbooks for foreign speakers; French language -- Grammar; French language -- Self-instruction.